The Validity of Credit Agreement Deeds Non-Compliant with the Law on the Office of Notaries: A Review from the Perspective of Legal Certainty and Accountability - Nadya, Siti Ahsanu (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
Credit agreement deeds executed before Notaries are intended to ensure legal certainty and strong evidentiary value in banking transactions. However, in practice, particularly within the banking sector, such deeds are frequently executed in violation of the formal requirements stipulated under the Law on the Office of Notaries (UUJN), including the absence of one party, non-simultaneous signing, and the failure to read the deed before all appearers. While previous studies have generally addressed formal obligations in notarial practice, limited attention has been given to the recurring practice of separate creditor signing and its legal implications. This study aims to examine the validity of credit agreement deeds that do not comply with the UUJN and to analyze the impact of such non-compliance on legal certainty and notarial accountability. Employing a normative juridical method, this research analyzes statutory regulations, legal doctrines, scholarly literature, and relevant judicial decisions concerning notarial law and the law of evidence. The findings demonstrate that non-compliance with mandatory formal requirements particularly the absence of simultaneous signing before the Notary results in the degradation of credit agreement deeds from authentic deeds to private deeds or, in certain cases, renders them legally invalid. Such degradation weakens evidentiary strength, undermines legal certainty for both creditors and debtors, and exposes Notaries to administrative, civil, and ethical liability. This study contributes to notarial law by clarifying the doctrinal boundaries of deed validity and reinforcing the essential relationship between legal certainty and notarial accountability.